ESP Academic Writing Hurdles: A Case Study of Technological Institute Freshmen - Anjar Nur Cholifah; Yuspik Yuspik; Irawansyah Irawansyah (Journal of English Language and Education, 2026)
This study explores ESP academic writing hurdles and coping strategies among freshmen at a technological institute. While previous research focuses on general EFL writing, studies specifically addressing the technical demands of engineering freshmen are limited. Using a qualitative case study, three students were interviewed for in-depth data. The data were analyzed using thematic analysis to categorize both writing hurdles and coping mechanisms. Results indicate that students face significant difficulties in lexical choices, grammar, text structure, and plagiarism, primarily due to limited academic vocabulary and the gap between high school and university standards. To cope, students combine course modules with peer discussions and digital resources. Findings suggest that lecturers should provide flexible feedback and support independent learning strategies. Ultimately, understanding these specific hurdles is crucial to help freshmen adapt to the demanding professional standards of technical academic writing.